Impaired Cytokine Responses to Live Staphylococcus epidermidis in Preterm Infants Precede Gram-positive, Late-onset Sepsis. (21st January 2020) - Strunk, Tobias; Hibbert, Julie; Doherty, Dorota; Nathan, Elizabeth; Simmer, Karen; Richmond, Peter; Currie, Andrew; Burgner, David
Abstract: Background: Late-onset sepsis (LOS) with Staphylococcus epidermidis is common in preterm infants, but the immunological mechanisms underlying heightened susceptibility are poorly understood. Our aim is to characterize the ontogeny of cytokine responses to live S. epidermidis in preterm infants with and without subsequent Gram-positive LOS. Methods: We conducted a prospective, observational cohort study of preterm infants (<30 weeks gestational age [GA]) with blood sampling on Days 1, 7, 14, 21, and 28 of life. Cytokine responses in peripheral whole blood stimulated with live S. epidermidis were analyzed by 11-plex immunoassay. Results: Of 129 infants (mean GA, 26.2 weeks; mean birth weight, 887g), 23 (17.8%) had confirmed LOS with Gram-positive organisms and 15 (11.6%) had clinical sepsis, with median onsets at 13 and 15 days, respectively. Blood cytokine responses to an in vitro S. epidermidis challenge were similar between infected and uninfected infants on Day 1, but diverged thereafter. Infants with subsequent LOS displayed broadly reduced S. epidermidis– induced responses from Day 7 onwards, compared to those who did not develop LOS. This pattern was observed with chemokines (interleukin [IL]-8, monocyte chemotactic protein–1, and macrophage inflammatory protein–1α), pro-inflammatory cytokines (IL-1, IL-6, and tumor necrosis factor–α) and the regulatory cytokine IL-10. Conclusions: Cytokine responses to a live S. epidermidis challenge are impaired in infants with LOS and precede the onset of clinical illness. Quantifying pathogen-specific cytokine responses at Day 7 may identify those high-risk preterm infants at the greatest risk of LOS, and prospective replication is warranted. Abstract : Preterm infants are uniquely susceptible to invasive bacterial infections, and predicting those at risk is currently not possible. The stimulation of peripheral blood with the common sepsis-causing pathogen, live Staphylococcus epidermidis, reveals impaired cytokine responses preceding the onset of sepsis.